Discovery of a cytochrome P450 enzyme catalyzing the formation of spirooxindole alkaloid scaffold - Nguyen, Tuan-Anh M.; Grzech, Dagny; Chung, Khoa; Xia, Zhicheng; Nguyen, Trinh-Don; Dang, Thu-Thuy T. (Frontiers in Plant Science, 2023)
Oxindole alkaloids from plants include compounds with an extensive range of biological activities such as anticancer, antibiotics, and anti-hypertension. However, the establishment and rationale of the oxindole scaffold biosynthesis are yet to be elucidated. Herein, we report the discovery and characterization of a cytochrome P450 enzyme (CYP) from kratom (Mitragyna speciosa) responsible for the formation of the spirooxindole alkaloids 3-epi-corynoxeine and isocorynoxeine from the corynanthe-type precursors. This discovery highlights the versatility of plant CYPs in building unusual alkaloid scaffolds and paves the way for accessing the spirooxindole pharmacophore and its derivatives.